Increasing Prevalence of Anxiety and Depression Disorders After Diagnosis of Chronic Pancreatitis: A 5-Year Population-Based Study. Issue 2 (February 2021) - Alkhayyat, Motasem; Abou Saleh, Mohannad; Coronado, Wendy; Abureesh, Mohammad; Al-otoom, Omaymah; Qapaja, Thabet; Mansoor, Emad; Simons-Linares, C. Roberto; Stevens, Tyler; Chahal, Prabhleen
Abstract : Objectives: Chronic pancreatitis (CP) is often associated with poor quality of life. Only a few small associative studies have reported the prevalence of mood disorders in CP. Using a large database, we sought to describe the epidemiology and risk association of anxiety and depression in CP and evaluate their outcomes. Methods: A multicenter database (Explorys), an aggregate of electronic health record data from 26 US healthcare systems, was surveyed. A cohort of patients with a diagnosis of CP between 2014 and 2019 was identified. Within this cohort, rates of anxiety and depression were calculated. Demographics, comorbidities, and outcomes were described. Results: Of the 30, 276, 810 individuals in the database (2014–2019), 67, 260 patients had a CP diagnosis (0.22%). When compared with patients with no history of CP, patients with CP were more likely to develop anxiety (odds ratio, 6.94; 95% confidence interval, 6.85–7.04) and depression (odds ratio, 5.09; 95% confidence interval, 5.01–5.17). Chronic pancreatitis patients with depression had an increased risk of suicidal ideation compared with controls. Conclusions: Patients with CP are at a higher risk of developing anxiety and depression compared with those without CP, with overall worse outcomes. Clinicians should screen CP patients and make appropriate referral to psychiatry when indicated.